The Solar Benefits of Al-Manar Al-Hafiziyah by the Author Shams Al-Din Muhammad Al-Qouj Hisari (d.841 AH) from Section Letters to Conditional Letters - Study and Verification - Abdullah , Atiyah; Mahmoud, Ismail (Islamic Sciences Journal, 2023)
The study dealt with : 1- The life of Al-Qawjhasari - may Allah have mercy on him - in terms of: his name, lineage, surname, birth, upbringing, qualities, scientific trips, sheikhs, works, and death -The Qawjisari - era politically, socially, and scientifically2 3- Adequate definition of a book - The Benefits of Solar for Al-Manar Al-Hafizia - in terms of: its name, its lineage to the author, the description of copies, the reason for its composition, its scientific value, and the author's methodology in the book. 4- The verified text according to the methodology that I have adopted. Among the findings: 1- Explanation of solar benefits is one of the medium annotations on board the Al-Manar, and this explanation is one of the best explanations, as the compiler has approached its explanation on board, expanded in explaining its phrases, and it is distinguished from other explanations with some benefits and pioneering, and its style is characterized by ease of expression, simplification of information, detail of evidence, discussion and weighting.. 2- The explanation is distinguished by citing many examples and jurisprudential issues with discussion, disagreement, evidence of litigants and the answer to them.